Roles of Genes in the Susceptibility to and Severity of Rheumatoid Arthritis - A Review (Journal of Medicine, 2012)
Rheumatoid arthritis (RA) is a chronic heterogeneous autoimmune disorder of unknown etiology. Genetic factors play an important role in susceptibility to RA as the heritability of RA is between 50% and 60%, with the human leukocyte antigen (HLA) locus accounting for at least 30% of overall genetic risk. It is conceivable that there is more than one susceptible gene(s) operative in RA, and an interaction of the relevant genes may predispose the offspring to develop the disease under certain conditions .Outside the major histocompatibility complex (MHC) region, some additional risk loci have been identified and validated including PTPN22, STAT4, PADI4, CTLA4 and others Genetic factors are also important in RA pharmacotherapy due to the gene-dependent activity of enzymes involved in the pharmacokinetics and/or pharmacodynamics of RA medications. Indeed, there is great variability in drug efficacy as well as adverse events associated with any anti-rheumatic therapy and genetics is thought to contribute significantly to this inter-individual variability in response. The ability to screen the entire genome for association to complex diseases has great potential for identifying gene effects. DOI: http://dx.doi.org/10.3329/jom.v13i1.10048 JOM 2012; 13(1): 51-54